Crystal forms and phase transformation of 1, 5‐pentanediamine‐terephthalate: a bio‐based nylon 5T monomer. Issue 4 (13th July 2020) - Li, Zihan; Yang, Pengpeng; Liu, Haodong; Liu, Jun; Zhu, Sha; Li, Xiaojie; Zhuang, Wei; Wu, Jinglan; Ying, Hanjie
Abstract : Monohydrate and anhydrate forms of PDA‐TPA crystal structures are determined and analysed, and the monohydrate shows favourable stability. The phase transition between the monohydrate and the anhydrate depends strongly on the temperature and water activity, and the larger the value of water activity is, the higher is the transition temperature. Abstract : Nylon 5T is one of the bio‐based nylons, its raw material 1, 5‐pentanediamine is derived from biomass resources and produced by biological methods. 1, 5‐pentanediamine‐terephthalate (PDA‐TPA) is the monomeric salt for nylon 5T polymerization, and its own product quality has a significant impact on the performance of nylon 5T. PDA‐TPA was prepared by anti‐solvent crystallization in this study. It exists in two solid forms, a monohydrate [form (I)] and an anhydrous phase [form (II)]. The transition temperature of the two phases was around 65°C in the given ethanol–water binary (7:1) mixture. The characterization of monohydrate and anhydrate phases regarding structures and stabilities was carefully carried out using powder X‐ray diffraction, single crystal X‐ray diffraction, differential scanning calorimetry, thermogravimetric analysis, hot‐stage microscopy and Fourier transform infrared spectroscopy. The relationship between the molecular interactions of monohydrate and anhydrate phases under different packing architectures and their thermal behaviours was analysed and established. In addition, the relationships between the structures and thermal behaviours for the two solid forms were analysed and established. In addition, the effect of solvent on phase conversion, the relationships between the temperature and water activity, as well as the relative stability of monohydrate and anhydrate phases under different thermodynamic conditions, were investigated by solid–solid transformation and solvent‐mediated transformation experiments. It was obvious that the transition temperature of monohydrate and anhydrate phases of PDA‐TPA was significantly influenced by water activity, and the larger the value of water activity is, the higher is the transition temperature. These studies give insight into the transformation of nylon 5T monomer salt and contribute to the control of target crystal preparation.